Respuesta :
Step 1: Simplify both sides of the equation.
x−7=15+3x
x+−7=15+3x
x−7=3x+15
Step 2: Subtract 3x from both sides.
x−7−3x=3x+15−3x
−2x−7=15
Step 3: Add 7 to both sides.
−2x−7+7=15+7
−2x=22
Step 4: Divide both sides by -2.
−2x/−2=22/−2
x=−11
Answer: [tex]x=.14.5[/tex]
Step-by-step explanation:
First, we need to get rid of the x on one side so the equation becomes solvable. Since one x has a coefficent and one doesn't, let's use the one without.
Remember that x and 1x are the same thing, since anything multiplied by one is itself.
[tex]3x - 1x - 2x[/tex]
So now we have-
[tex]-7 = 15 + 2x[/tex]
Now it looks a little easier, right? First we get rid of the 15-
[tex]15-15 =0\\-7-15 =-22[/tex]
So now we have-
[tex]-22 = 2x[/tex]
Let's get rid of the coefficent now by dividing by two.
[tex]\frac{2x}{2} =x\\\frac{-22}{2} =-14.5[/tex]
So [tex]x=.14.5[/tex]